HETEROSIS STUDIES FOR EARLINESS, FRUIT YIELD AND YIELD ATTRIBUTING TRAITS IN CHILLI (CAPSICUM ANNUM L.) - SONAM SPALDON, SHARAFAT HUSSAIN, NAYEEMA JABEEN PADMA LAY (The Bioscan, 2015)
A study was conducted in chilli to estimate the magnitude of heterosis for earliness, fruit yield and its eleven yield attributing traits. Thirty F1 hybrids were derived from crosses between ten female lines and three testers using line × tester analysis and these F1s along with parents were evaluated during kharif 2010-11 using Randomized Block Design. A wide range of heterosis over better parent was observed in F1 generation for yield per hectare and its attributing traits. Among 30 F1s crosses, crosses SC-304 × Arka Lohit and SC-277 × Local had revealed the highest significant desirable heterobeltiosis for early maturity. The crosses SC-502 × Arka Lohit was recognized as the best heterotic cross for fruit yield per hectare as it exhibited highest positive over better parent. Hence, they could be further evaluated to exploit the heterosis or utilized in future breeding programmes to obtain desirable segregates for the development of superior genotypes